1988
DOI: 10.1139/g88-007
|View full text |Cite
|
Sign up to set email alerts
|

Cytological evidence bearing on the origin of the B genome in polyploid wheats

Abstract: To help elucidate the origin of the B genome in polyploid wheats, karyotypes of Triticum turgidum, Triticum monoccum, and all six purported B genome donors were compared. The analysis utilized a common cytological procedure that employed the most advanced equipment for the measurement of chromosome lengths at metaphase in root tip cells. A comparison of the karyotypes of T. turgidum and T. monococcum permitted the identification of B genome chromosomes of T. turgidum. These consist of two SAT pairs, one ST pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…6). Similar conclusions have been reached by Kerby and Kuspira (1988) from karyotypic studies, and by Natarajan and Sarma (1974) from comparisions of chromosome banding patterns.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…6). Similar conclusions have been reached by Kerby and Kuspira (1988) from karyotypic studies, and by Natarajan and Sarma (1974) from comparisions of chromosome banding patterns.…”
Section: Discussionsupporting
confidence: 78%
“…searsii is the probable donor of the B genome since it is the only species in the Sitopsis section that has a sympatric distribution with both T. turgidurn and T. monococcum, and its satellite chromosomes show the same morphology as that of chromosomes I B and 6B of T. aestivum (Feldman, 1978). The karyotypic analysis carried out by Kerby and Kuspira (1988) seems to indicate the same conclusions. Ae.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Vakhitov & Gimalov (1988) compared the 5S ribosomal RNA and Kerby & Kuspira (1988), using cytogenetic evidence, concluded that the five species were more or less equally related to one another. Yen & Kimber (1990) All five species were found to be primarily autogamous.…”
Section: Variation In Aegilops 625mentioning
confidence: 99%